The analysis of survival of the patients with lymphoproliferative desorders at presence or lack of the myelodisplasia - N. Yu. D’yachkova; T. I. Pospelova; I. B. Kovynev; Yu. N. Obgolts (Бюллетень сибирской медицины)
.